Recognizing the fundamental flaw in our dietary studies investigating the impact diets, drugs and lifestyle have on preventing or reversing CAD - Richard M Fleming; Matthew R Fleming; Tapan K Chaudhuri (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Since the introduction of the (a) Inflammation and Heart Disease, and (b) Angina, Theories in the mid-1990s, a transition from a cholesterol only etiology for coronary artery disease (CAD) has taken place; resulting in an understanding that CAD is the result of an Inflammatory process precipitated by a number of factors-including, but not limited to LDL cholesterol and saturated fat [1-5], which impair coronary blood flow.